Biosynthesis, classification, properties, and applications of Weissella bacteriocins - Singh, Jahnavi Kumari; Devi, Palanisamy Bruntha; Reddy, G. Bhanuprakash; Jaiswal, Amit K.; Kavitake, Digambar; Shetty, Prathapkumar Halady (Frontiers in Microbiology, 2024)
This review aims to comprehensively chronicle the biosynthesis, classification, properties, and applications of bacteriocins produced by Weissella genus strains, particularly emphasizing their potential benefits in food preservation, human health, and animal productivity. Lactic Acid Bacteria (LAB) are a class of microorganisms well-known for their beneficial role in food fermentation, probiotics, and human health. A notable property of LAB is that they can synthesize antimicrobial peptides known as bacteriocins that exhibit antimicrobial action against both closely related and other bacteria as well. Bacteriocins produced by Weissella spp. are known to exhibit antimicrobial activity against several pathogenic bacteria including food spoilage species, making them highly invaluable for potential application in food preservation and food safety. Importantly, they provide significant health benefits to humans, including combating infections, reducing inflammation, and modulating the gut microbiota. In addition to their applications in food fermentation and probiotics, Weissella bacteriocins show promising prospects in poultry production, processing, and improving animal productivity. Future research should explore the utilization of Weissella bacteriocins in innovative food safety measures and medical applications, emphasizing their potential to combat antibiotic-resistant pathogens, enhance gut microbiota composition and function, and synergize with existing antimicrobial therapies.